Our sisters' keepers : nineteenth-century benevolence literature by American women - Bergman, Jill, 1963-; Bernardi, Debra, 1954- (Studies in American literary realism and naturalism., 2005)
Essays on the roles played by women in forming American attitudes about benevolence and poverty relief. American culture has long had a conflicted relationship with assistance to the poor. Cotton Mather and John Winthrop were staunch proponents of Christian charity as fundamental to colonial American society, while transcendentalists harbored deep skepticism towards benevolence in favor of Emersonian self-reliance and Thoreau?s insistence on an ascetic life. Women in the 19th century, as these essays show, approached issues of benevolence far differently than their male counterparts, consistent.